Betting on Exports: Trade and Endogenous Heterogeneity - Alessandra Bonfiglioli; Rosario Crinò; Gino Gancia (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study the equilibrium determinants of firm-level heterogeneity in a model in which firms can affect the variance of their productivity draws at the entry stage and explore the implications in closed and open economy. By allowing firms to choose the size of their investment in innovation projects of unknown quality, the model yields a Pareto distribution for productivity with a shape parameter that depends on industry-level characteristics. A novel result is that export opportunities, by increasing the payoffs in the tail, induce firms to invest in bigger projects with more spreadout outcomes. Moreover, when more productive firms also pay higher wages, trade amplifies wage dispersion by making all firms more unequal. These results are consistent with new evidence on howfirm-level heterogeneity and wage dispersion vary in a panel of U.S. industries. Finally, we use patent data across U.S. states and over time to provide evidence in support of a specific mechanism of the model, namely, that export opportunities increase firmheterogeneity by fostering innovation.
Keywords: F12; F16; E24; 330; firm heterogeneity; productivity dispersion; wage inequality; international trade